Migration Robots: Dialogue, the Space in Between, the Section of a Construct That Does Not Exist - Guillermo Garita (Oz, 2005)
This essay is written under several assumptions, which give me the opportunity to establish a platform of reference for my work, my work within my practice and the work within my academic studio.